THE EFFECTS OF INTERNAL GREEN MARKETING ON JOB SATISFACTION AND FINANCIAL OUTCOMES – THE CASE OF THE SERBIAN AGRIBUSINESS SECTOR - Vesna Milanović; Vesna Miletić; Aleksandra Jagodić Rusić; Jasmina Poštin (Ekonomika Poljoprivrede (1979))
The purpose of this paper was to examine the effects of internal green marketing (IGM) on managers’ job satisfaction (JS) and organizational financial outcomes (FOs). An online survey was used to collect data. On the sample of 78 managers of medium-sized and large organizations in the Serbian agribusiness sector, using partial least squares structural equation modeling technique, the results showed that IGM positively affects managers’ JS and FOs of the organizations. They also revealed that managers’ JS affects FOs, but also partially mediates the link between IGM and FOs. These results emphasize the significant role of IGM in improving managers’ JS and organizational FOs, but the importance of nurturing managers’ JS as one of the job related attitudes. The main contribution of this paper is the establishment of the link between these variables, as well as the testing of the assumed relationships in the agribusiness context in which the relationships between these variables have not been tested before.